3D Facial Morphometry in Children with Oral Clefts. (July 2014) - Bugaighis, I.; Mattick, C.R.; Tiddeman, B.; Hobson, R.
Objectives: The aim of this study was to characterize three-dimensional (3D) facial morphological variation of children with cleft lip and palate compared to an age- and sex-matched control group. Design: Cross-sectional, case-controlled observational morphometric study. Materials and Methods: Subjects were 103 children aged 8 to 12 years old with cleft lip and palate—40 with unilateral cleft lip and palate, 23 with unilateral cleft lip and alveolus, 19 with bilateral cleft lip and palate, and 21 with isolated cleft palate (ICP)—and 80 sex- and age-matched control subjects. Subjects were scanned using 3D stereophotogrammetry. Thirty-nine landmarks were digitized for each scan, and the x, y, and z coordinates for each landmark were extracted. Linear and angular facial measurements were computed. Multivariate analysis of covariance was undertaken to detect significant differences in facial morphometry between the groups. Results: Statistically significant differences ( P < .05) were observed between all groups. The greatest morphometrical impact was seen in those groups where both lip and palate were affected and repaired; the group with ICP was the most similar to the control subjects. Conclusions: Significant differences were seen in 3D soft-tissue measurements, mainly in the nasolabial region, between the cleft groups where the lip is affected and the ICP and control groups.